Distinctive organized molecular assemble of MoS2, MOF and Co3O4, for efficient dye-sensitized photocatalytic H2 evolution. Issue 9 (12th April 2018) - Fan, Kai; Jin, Zhiliang; Wang, Guorong; Yang, Hao; Liu, Duanduan; Hu, Hongyan; Lu, Gongxuan; Bi, Yingpu
Abstract : Stable and efficient photocatalyst has been a key research goal in recent years. Abstract : Stable and efficient photocatalyst has been a key research goal in recent years. Based on the dominant performances of MoS2, metal organic frameworks (MOFs) and Co3 O4 themselves, for example, MoS2 has superior electronic properties, MOFs have a large specific surface area and Co3 O4 has a suitable band gap to give a visible light response, and with a view to overcome the disadvantages of MoS2, MOFs and Co3 O4 individually, for example, the poor stability of MOFs, cobalt ions being easily released from Co3 O4, a distinctive organized molecular assemble of MoS2, MOF and Co3 O4 was successfully designed and assembled with the shape of a leaf. Namely, the special structure of MoS2 –MOF appears as a leaf, and Co3 O4 looks like the venation. More importantly, an efficient dye-sensitized photocatalytic H2 evolution was obtained. For instance, when the content of Co3 O4 was at 30%, the photocatalytic hydrogen production could reached up to 450.13 μmol in the EY-sensitized system under visible light irradiation within 5 hours. Moreover, the organized molecular assembled Co3 O4 greatly improved the stability of the photocatalyst. Here, MoS2 and a metal organic framework (MOF) were combined to form a new structure catalyst MoS2 –MOF, which provided a large specific surface area and sufficient active sites, the MoS2 gave excellent electronic and optoelectronic properties and greatly improved the electron transport efficiency. The MoS2 –MOF/Co3 O4 catalyst has a great fluorescence quenching rate, and the lifetime of the electron is also greatly improved. A peculiar synergetic effect of MoS2 and Co3 O4 on the MOF for photocatalytic hydrogen evolution is revealed and the synergy of MoS2 and Co3 O4 is the most critical factor. The above phenomena are supported by a series of characterization results such as SEM, XRD, TEM, EDX, XPS, BET, UV-vis DRS, FTIR, transient fluorescence and electro-chemistry, and so forth and the results of which were in good agreement with each other.